Heat transfer in aerospace applications - Sundén, Bengt; Fu, Juan (Academic Press, 2017)
Heat Transfer in Aerospace Applications is the first book to provide an overall description of various heat transfer issues of relevance for aerospace applications. The book contains chapters relating to convection cooling, heat pipes, ablation, heat transfer at high velocity, low pressure and microgravity, aircraft heat exchangers, fuel cells, and cryogenic cooling systems.